Cover Feature: Profiling Heparan Sulfate‐Heavy Metal Ions Interaction Using Electrochemical Techniques (Chem. Eur. J. 55/2022). Issue 55 (15th September 2022) - Shitrit, Ariel; Mardhekar, Sandhya; Alshanski, Israel; Jain, Prashant; Raigawali, Rakesh; Shanthamurthy, Chethan D.; Kikkeri, Raghavendra; Yitzchaik, Shlomo; Hurevich, Mattan
Abstract : The connection between heparan sulfate molecular components and heavy metal ion binding is largely unknown because of the complexity and the heterogeneity of the polysaccharide, which limit the ability to study those interactions. By assembling rationally designed synthetic heparan sulfates on surfaces, we have developed new ways to correlate glycan stereochemistry and sulfate group regiochemistry with heavy metal ion binding and selectivity. More information can be found in the Research Article by R. Kikkeri, S. Yitzchaik, M. Hurevich, and co‐workers (DOI: 10.1002/chem.202202193 ).